2017
DOI: 10.1159/000481846
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Microrna-22 Against Endothelial Cell Injury by Targeting NLRP3 Through Suppression of the Inflammasome Signaling Pathway in a Rat Model of Coronary Heart Disease

Abstract: Background/Aims: This study aimed to identify the role of microRNA-22 (miR-22) in endothelial cell (EC) injury in coronary heart disease (CHD) by targeting NLRP3 through the inflammasome signaling pathway. Methods: A total of 24 healthy male Sprague-Dawley (SD) rats were divided into normal and atherosclerosis groups. The atherosclerosis rats were assigned into blank, negative control (NC), miR-22 mimic, miR-22 inhibitor and miR-22 inhibitor + siNLRP3 groups. A luciferase reporter gene assay was used to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The study showed that miR-495 and miR-551a suppressed the invasion and migration of human gastric cancer cells by directly mediating with phosphatase of regenerating liver-3 [43]. MiR-22 restrains apoptosis and improves cell activity in endothelial cell (EC) injury under coronary heart disease (CHD) stress, and the role of NLRP3 is the opposite [44]. Moreover, the NLRP3 inflammasome regulates contrast-media-induced acute kidney damage through controlling cell apoptosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that miR-495 and miR-551a suppressed the invasion and migration of human gastric cancer cells by directly mediating with phosphatase of regenerating liver-3 [43]. MiR-22 restrains apoptosis and improves cell activity in endothelial cell (EC) injury under coronary heart disease (CHD) stress, and the role of NLRP3 is the opposite [44]. Moreover, the NLRP3 inflammasome regulates contrast-media-induced acute kidney damage through controlling cell apoptosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, employing NLRP3 targeting miRNA might serve as a successful therapeutic approach for the treatment of thrombotic features (Huang et al, 2017;Neudecker et al, 2017). Huang et al (2017), demonstrated the effect of miR-22 in lowering the levels of pro-inflammatory cytokines by inhibiting the NLRP3 inflammasome pathway, which suppresses coronary arterial ECs apoptosis in rats with coronary heart disease. miRNA regulation of NLRP3 inflammasome is very well documented.…”
Section: Inflammasome In Endothelial Activationmentioning
confidence: 99%
“…NLRP3 is also a direct target of miR-20b-5p, upregulation of which alleviates Mycobacterium tuberculosis-induced inflammation in murine lung tissue (54). Additionally, miR-22-3p downregulates NLRP3 expression, and this miRNA is decreased in injured coronary arterial endothelial cells in a rat model of high-fat diet-induced coronary heart disease, whereas upregulation of miR-22-3p exerts a protective effect on cell survival (55). The expression of miR-133b-3p, which also targets NLRP3, is reduced in the nasal mucosa of a mouse model of allergic rhinitis (56).…”
Section: Mirnas Target Inflammasome Componentsmentioning
confidence: 99%